Perancangan Website Sistem Pakar Menentukan Tingkat Kemampuan dalam Public Speaking menggunakan Metode Extrime Programming - Dila Anugrah; Fajar Ratnawati (STIKes Ibnu Sina Ajibarang, 2024)
This research presents an expert system using the extreme programming method to determine the level of ability in public speaking. Public Speaking is an important speaking skill in many fields, but it is often difficult for individuals to evaluate their ability. The extreme programming method is used to provide a reliable level of workmanship in the public speaking system. The expert system will provide recommendations in the form of solutions, or strategies that can help individuals improve their public speaking skills. individuals in improving their public speaking skills. The solutions provided will be adjusted to the individual's ability level, so as to provide effective knowledge. The trust method used is the certainty factor method. The results displayed are information about level of public speaking ability, the level of confidence of an expert along with solutions that can be done next by website users.